Assessment and analysis of the intellectual potential of universities in the Republic of Bashkortostan - L. R. Khabibullina (Статистика и экономика)
In the conditions of increasing competition in the market of educational services, one of the main tasks of the university management is the effective management of its intellectual potential. This will make it possible to increase the competitiveness of Russian universities. To effectively manage the intellectual potential of an educational institution, its objective evaluation is necessary. Evaluation of the intellectual capacity of the educational institution will allow to quickly manage the activity of the university and determine those areas of innovative development that will ensure its competitiveness, stability and flexibility in changing external conditions.Currently, there is a wide variety of methods for assessing intellectual potential, but insufficiently developed techniques directly applied to the analysis and evaluation of the intellectual potential of a higher education institution. Therefore, the problem of developing a single, universal methodology for assessing intellectual potential, which would allow the most accurate, objective assessment of the intellectual potential of the university, remains urgent. This is due to the fact that the very notion of intellectual potential is relatively new and there are contradictions regarding the definition of its content and structure.The correct choice of the system of indicators, which allows to characterize the potential in a variety of ways in a complex manner, and the choice of the most reliable method for its evaluation will ensure the objectivity of evaluating the intellectual potential of the university. The purpose of this study is the approbation of the proposed system of indicators and methodology for assessing the intellectual potential of the university on the example of universities in the Republic of Bashkortostan.The research materials are based on the results of monitoring the activities of educational institutions of higher education. Methods of research include the method of paired comparisons, a method of comparative analysis.Results of the research: a system of indicators for evaluating the intellectual potential of higher education institutions and a methodology for its evaluation were proposed, an assessment of intellectual potential was made using the example of five universities of the Republic of Bashkortostan and their comparative analysis. Based on the results of the comparative analysis of the universities of the Republic of Bashkortostan, the relevant conclusions were drawn. The system of indicators proposed in the study and the methodology for evaluating the intellectual potential of the university make it possible to determine the capabilities of the university in the implementation of innovative activity and to make effective management decisions.